Kinetic Study on Preparation of High-Purity Enriched Boric-10 Acid Used in Nuclear Power Plants - Zhang, Weijiang; Wang, Xiangmei; Xu, Jiao (Asian Journal of Chemistry, 2015)
Although entiched boron-10 trifluoride had been industrialized, it can not be applied to nuclear industry or other fields directly. To take advantages of the superior features of boron-10 isotope, boron-10 trifluoride should be inverted into boric-10 acid (H310BO3). The study of reaction of boron trifluoride methanol complex with aqueous solution of lithium hydroxide is rare. In this paper, mechanism of the reaction was discussed as well as proper reaction conditions like reaction temperature, the mass of water and the ratio of reactants were determined. The kinetics of the system were examined using homogeneous kinetic models and was determined to be a pseudo-second-order homogeneous reaction control model. The activation energy was calculated to be 43.67 kJ/mol.